PENGARUH PENERAPAN QUANTUM QUOTIENT TERHADAP PRESTASI BELAJAR PAI PESERTA DIDIK (FAI- Undar, 2017)
Quantum Quotient Strategy can boost IQ, EQ and SQ students by it‟s various stages. Help memory, active right brain function, because children are trained to use their imagination, make songs, and combine the words. So, that material becomes unique, interesting and fun.While the problem is how the implementation of the Quantum Quotient strategy on the subjects of PAI, how student achievement in subjects PAI, is there any influence Quontient Quantum strategy in improving student achievement in Vocational State High School of Geger Madiun.In this study, the authors use a simple linear regression method, this method is a type of quantitative research with a deductive approach, or the methods used are observation, interviews, documentation, questionnaire. While the analysis is used to perform data analysis for validity, reliability test and F test.From the results of the study, the effect of the use of Quantum Quotient strategy in teaching and learning subjects of Islamic Education students class X in Vocational State High School of Geger Madiun is good. This is indicated by the average percentage is 61.11%. In addition, Quantum Quotient Strategy also affect the results of learning achievement. It is known from student achievement of Islamic Education in Vocational State High School of Geger Madiun, this is indicated by the average value of 73.38 which was taken from the report cards are modified by the value of tasks, and daily tests and consulted the semester test. Therefore we can conclude there was an effect of signification Quantum Quotient strategy towards learning achievement of Islamic Religious Education subjects. It can be known from there are some differences student achievement before and after it is applied Quantum Quotient, is seen from the live lines sthat had they only listened to the teacher and did not dare to speak one's mind, now they dare to question and issued an advisory opinion, the motivation is now more improved student learning, students are also more creative.